2021
DOI: 10.1080/09205063.2021.1900652
|View full text |Cite
|
Sign up to set email alerts
|

Loading of doxorubicin on poly(methyl methacrylate-co-methacrylic acid) nanoparticles and release study

Abstract: Nanoparticles (NP) of 12.7 nm in diameter of the poly(methyl methacrylate (MMA)-co-methacrylic acid (MAA)) copolymer were prepared. 13 C-NMR results showed a MMA:MAA molar ratio of 0.64:0.36 in the copolymer, which is similar to the poly(MMA-co-MAA) commercially known as the FDA approved Eudragit S100 (0.67:0.33). The NP prepared in this study were loaded at pH 5 with varying amounts (from 0.54 to 6.91%) of doxorubicin (DOX), an antineoplastic drug. 1 H-NMR results indicated the electrostatic interactions betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…Furthermore, in 2021, López-Muñoz et al prepared polymeric nanoparticles containing DOX. It was found that the DOX loading capacity (DLC) into the polymeric nanoparticle was variable, ranging from 0.54 to 6.91%, which is consistent with our DOX LC% (5.37%) …”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore, in 2021, López-Muñoz et al prepared polymeric nanoparticles containing DOX. It was found that the DOX loading capacity (DLC) into the polymeric nanoparticle was variable, ranging from 0.54 to 6.91%, which is consistent with our DOX LC% (5.37%) …”
Section: Resultssupporting
confidence: 93%
“…It was found that the DOX loading capacity (DLC) into the polymeric nanoparticle was variable, ranging from 0.54 to 6.91%, which is consistent with our DOX LC% (5.37%). 50 3.7. In Vitro DOX Release Study.…”
Section: Resultsmentioning
confidence: 99%
“…The PNA nanogel core obtained a poly (N-isopropylacrylamide) (PNIPAM) group that shows thermo-sensitive phase transition properties [177,187,188]. The anticancer drug doxorubicin (DOX) was loaded in the PNA nanogel via electrostatic interaction [186,189,190]. This drug exhibited an accelerated release under low pH conditions, occurring during the endocytosis process in cancer cells [186,189,191,192].…”
Section: Photo-responsive Nanoparticle Drug-delivery Systems For Anti...mentioning
confidence: 99%
“…Therefore, this developed nanoparticle exhibited the selective delivery of anticancer drugs spatiotemporally due to its active targeting ability and photo-induced release properties, in addition to photo-induced cancer tissue ablation for enabling effectively synergistic anticancer therapy. nanogel via electrostatic interaction [186,189,190]. This drug exhibited an accelerated release under low pH conditions, occurring during the endocytosis process in cancer cells [186,189,191,192].…”
Section: Photo-responsive Nanoparticle Drug-delivery Systems For Anti...mentioning
confidence: 99%